2015
DOI: 10.1124/mol.115.098756
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Sugars as Extracellular Signaling Molecules: Cellular and Physiologic Consequences of P2Y14 Receptor Activation

Abstract: UDP-sugars, which are indispensable for protein glycosylation reactions in cellular secretory pathways, also act as important extracellular signaling molecules. We discuss here the broadly expressed P2Y 14 receptor, a G-protein-coupled receptor targeted by UDP sugars, and the increasingly diverse set of physiologic responses discovered recently functioning downstream of this receptor in many epithelia as well as in immune, inflammatory, and other cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 65 publications
1
91
0
Order By: Relevance
“…The P2Y 14 R is a Gi-coupled receptor that is activated by UDP-sugars with a relative potency order of UDP-glucose > UDP-galactose > UDP-glucuronic acid > UDP-Nacetylglucosamine [13,14]. UDP also is an agonist of this receptor, but ATP, UTP, or other naturally occurring nucleoside 5′-di-or triphosphates have no P2Y 14 R activity [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P2Y 14 R is a Gi-coupled receptor that is activated by UDP-sugars with a relative potency order of UDP-glucose > UDP-galactose > UDP-glucuronic acid > UDP-Nacetylglucosamine [13,14]. UDP also is an agonist of this receptor, but ATP, UTP, or other naturally occurring nucleoside 5′-di-or triphosphates have no P2Y 14 R activity [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…UDP also is an agonist of this receptor, but ATP, UTP, or other naturally occurring nucleoside 5′-di-or triphosphates have no P2Y 14 R activity [13][14][15][16]. P2Y 14 R mRNA expression has been reported in the brain and several peripheral tissues [13], including the lung, circulating neutrophils, and other immune/inflammatory cells [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…32 To date, a clear role for this receptor has only been established in human neutrophils, where it contributes to chemotaxis. 80 Further studies will be required to evaluate its role in various inflammatory situations.…”
Section: P2y 14 Receptormentioning
confidence: 99%
“…The P2Y14 receptor subtype, the only officially-recognized P2Y purinergic receptor activated by uridine sugars (i.e. UDP-glucose and UDP-galactose) which is expressed by leukocytes and promotes neutrophil chemotaxis (Lazarowski et al, 2015), has been found upregulated in spinal microglia after peripheral nerve injury (Kobayashi et al, 2012). The demonstration that its activation on microglia cells reduced the proliferation of astrocytoma cells in in vitro cocultures (Curet & Watters, 2018) suggests that it may represent an additional member of the purinergic network controlling astrocyte-to-microglia communication in the brain in pathological conditions, possibly including pain.…”
Section: Contribution Of Spinal Astrocytes To Neuropathic Pain: a Rolmentioning
confidence: 99%